An unusual cause of granulomatous colitis: Behcet's disease. Issue 2 (15th August 2019) - Yadav, Ashutosh I; Chattopadhyay, Arghya; Ahamed, Rizwan; Muktesh, Gaurav; Narang, Tarun; Nada, Ritambhra; Sharma, Aman; Mandavdhare, Harshal; Sharma, Vishal; Dutta, Usha
Abstract : Intestinal involvement in Behcet's disease (BD) is uncommon. Differentiating it from close mimics like Crohn's Disease is difficult. Further, in asymptomatic cases, diagnostic challenges posed is still greater. A 17‐year‐old boy had history of recurrent oro‐genital ulcers, papulo‐pustular skin eruptions, ocular lesions and had presented with recent onset perianal abscess. Fecal calprotectin was elevated, and ileo‐colonoscopy showed ileocolonic ulcers of inflammatory nature. Clinical diagnosis of intestinal BD was made. Patients with BD having mucosal lesions may harbor asymptomatic intestinal lesions. Screening them with fecal calprotectin levels and if positive, with subsequent imaging and endoscopic biopsy with timely initiation of appropriate treatment in such asymptomatic cases help to control overall disease activity. Abstract : Many diseases can cause intestinal granulomas like Crohn's disease and tuberculosis. Behcet's disease is an uncommon cause of intestinal granulomas. Here, we present the case of intestinal Behcet's that closely mimicked Crohn's disease.